2012
DOI: 10.1016/j.jedc.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical information and the rate of information diffusion

Abstract: a b s t r a c tThe rate of information diffusion and, consequently, price discovery are conditional not only upon the design of the market microstructure but also the informational structure. This paper presents a market microstructure model showing that an increasing number of information hierarchies among informed competitive traders leads to a slower information diffusion rate and informational inefficiency. The model illustrates that informed traders may prefer trading with each other rather than with nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Hong and Stein [7] verified the tendency for stock prices to react to information through a behavioral model. Based on this, many studies have directly incorporated information diffusion as an important factor in stock pricing, and the results indicate that information diffusion could explain the fluctuation of stock prices in different periods [8][9][10]. According to empirical evidence, it was found that proxy variables of information diffusion would exert a great influence on stock price fluctuations [11][12][13].…”
Section: Related Literaturementioning
confidence: 99%
“…Hong and Stein [7] verified the tendency for stock prices to react to information through a behavioral model. Based on this, many studies have directly incorporated information diffusion as an important factor in stock pricing, and the results indicate that information diffusion could explain the fluctuation of stock prices in different periods [8][9][10]. According to empirical evidence, it was found that proxy variables of information diffusion would exert a great influence on stock price fluctuations [11][12][13].…”
Section: Related Literaturementioning
confidence: 99%